A WAY TOWARDS DOPING IN SPORTS: CHALLENGES AND ADVANCES - Sheikh, Mohammed Ajaz (ShodhKosh: Journal of Visual and Performing Arts, 2025)
Doping is a public health problem, not just a problem in the professional sports community. It is a complex and ancient phenomenon, due to the wide range of substances transported through both legal and illegal trade routes. It occurs in elite athletes, but it also affects recreational athletes and was generally considered dangerous and unhealthy.It directly affects sports, competitions around the world. Blood doping refers to the misuse of certain substances to increase the mass of red blood cells so that the body can transport more oxygen to the muscles and thus improve the performance and endurance of a player or person. It lists many life-threatening side effects of blood doping, such as increased blood viscosity, myocardial infarction, embolism, stroke, infections, allergic reactions and a certain risk of blood-related diseases such as HIV, hepatitis, etc. Anti-doping policies established by individual sports governing bodies may conflict with local laws. There is no such connection between these authorities and the laws of the government. Today players use many techniques and drugs, which makes it difficult for them to be detected by experts and in the fight against doping. However, it is our duty to fight against them by updating information and events.